2017
DOI: 10.1038/srep45106
|View full text |Cite
|
Sign up to set email alerts
|

Chymase-producing cells of the innate immune system are required for decidual vascular remodeling and fetal growth

Abstract: Intrauterine growth restriction (IUGR) is caused by insufficient remodeling of spiral arteries (SAs). The mechanism underlying the relevance of natural killer cells (NKs) and mast cells (MCs) for SA remodeling and its effects on pregnancy outcome are not well understood. We show that NK depletion arrested SA remodeling without affecting pregnancy. MC depletion resulted in abnormally remodeled SAs and IUGR. Combined absence of NKs and MCs substantially affected SA remodeling and impaired fetal growth. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 62 publications
1
67
0
Order By: Relevance
“…Interestingly, a combined absence of MCs and NKs worsens SA remodeling when compared to single cell deficiency, suggesting that these 2 cell types have similar functionalities at least regarding SA remodeling. 115,116 We found that α-chymase Mcpt5, secreted by MCs and uNKs, is able to induce the apoptosis of uterine smooth muscle cells, a process that is very important for an efficient SA remodeling. 116 182,183,127 In guinea pig and human, it has been shown that serotonin, histamine, and prostaglandin are central players for the stimulation of the myometrial contractility as initiators of birth.…”
Section: Influence Of Umcs On Implantation and Tissue Remodeling Dumentioning
confidence: 95%
See 4 more Smart Citations
“…Interestingly, a combined absence of MCs and NKs worsens SA remodeling when compared to single cell deficiency, suggesting that these 2 cell types have similar functionalities at least regarding SA remodeling. 115,116 We found that α-chymase Mcpt5, secreted by MCs and uNKs, is able to induce the apoptosis of uterine smooth muscle cells, a process that is very important for an efficient SA remodeling. 116 182,183,127 In guinea pig and human, it has been shown that serotonin, histamine, and prostaglandin are central players for the stimulation of the myometrial contractility as initiators of birth.…”
Section: Influence Of Umcs On Implantation and Tissue Remodeling Dumentioning
confidence: 95%
“…This challenging balance between immunity and specific tolerance requires a perfectly coordinated interplay of immune cells. 115 In addition, T cells, DCs, NK cells, neutrophils, macrophages, and MCs are present at the interface between mother and fetus.…”
Section: Ma S T Cell S and Reproduc Ti Onmentioning
confidence: 99%
See 3 more Smart Citations